Giải toán

Có 1 trả lời

  1. \[\mathop {\lim }\limits_{x \to 1} \frac{{x + {x^2} + … + {x^n} – n}}{{x – 1}}\]
    \[ = \mathop {\lim }\limits_{x \to 1} \frac{{\left( {x – 1} \right) + \left( {{x^2} – 1} \right) + … + \left( {{x^n} – 1} \right)}}{{x – 1}}\]
    \[ = \mathop {\lim }\limits_{x \to 1} \left( {1 + \left( {x + 1} \right) + \left( {{x^2} + x + 1} \right) + … + \left( {{x^{n – 1}} + {x^{n – 2}} + … + 1} \right)} \right)\]
    \[ = 1 + 2 + 3 + … + n = \frac{{n\left( {n + 1} \right)}}{2}\]

Để lại nhận xét

%d bloggers like this: